A pilot genome wide association and gene expression array study of suicide with and without major depression. (December 2013) - Galfalvy, Hanga; Zalsman, Gil; Huang, Yung-Yu; Murphy, Lauren; Rosoklija, Gorazd; Dwork, Andrew J.; Haghighi, Fatima; Arango, Victoria; Mann, J. John
Abstract Objectives. Suicide is partly heritable but the responsible genes have not been identified. We conducted a gene-centric, low coverage single nucleotide polymorphism (SNP) pilot genome-wide association study (GWAS) seeking new candidate regions in suicides with and without depression, combined with gene expression assay of brain tissue. Methods. Ninety-nine Caucasian subjects, including 68 who completed suicide and 31 who died suddenly from other causes, were genotyped postmortem using GeneChip® Mapping 50K Xba. Clinical data were obtained from relatives. SNPs with Hardy–Weinberg equilibrium P values below 0.001 were excluded from analysis. Illumina chip expression arrays assayed the transcriptome in prefrontal cortex in a drug-free subgroup. Results. GWAS analysis (cutoff P < 0.001) yielded 58 SNPs, 22 of them in or near 19 known genes, with risk allele-associated odds ratios between 2.7 and 6.9. Diagnosis of mood disorder did not explain the associations. Some of the SNPs matched into four functional groups in gene ontology. Gene expression in the prefrontal and the anterior cingulate cortex for these 19 genes was measured on a separate, though overlapping, sample of suicides and seven of 19 genes showed altered expression in suicides as compared with controls, especially in immune system related genes. Conclusions. Matching GWAS findings with expression data assesses functional effect of new candidate genes in suicide, and is an alternative form of confirmation or replication study. Results highlight a role for neuroimmunological effects in suicidal behaviour.